Dissecting Patterns of Hospital Civil Liability in Medical Disputes: Between Vicarious Liability and Central - yansen ones mambrasar; Yohana Watofa; Jonhi Sassan (Indonesian Scientific Publication, 2024)
This research discusses the civil liability of hospitals in Indonesia in the context of medical malpractice. The purpose of this study is to explore the application of the principles of vicarious liability and corporate responsibility in the civil liability of hospitals for the acts of doctors working under the auspices of the hospital. The research method involves analyzing legal documents and medical malpractice cases in Indonesia. The results show that hospitals in Indonesia can be sued for damages for the acts or mistakes of their workers and agents as well as for their own mistakes. The principle of vicarious liability emphasizes that hospitals can be held liable for errors or omissions committed by doctors, nurses, or other medical personnel while they are serving under the auspices of the hospital. This research also shows that hospitals should ensure compliance with applicable regulations and procedures and conduct effective risk management to reduce the likelihood of medical disputes and the potential financial impact that could arise from legal claims. The contribution of this study is in improving the understanding of the legal liability of hospitals in medical malpractice cases and providing guidance for hospitals in developing and implementing better policies and procedures to reduce the risk of medical errors. The recommendation of this study is that hospitals should ensure that all their medical staff adhere to established medical standards and conduct effective risk management to reduce the likelihood of medical disputes and the potential financial impact that could arise from legal claims.